Pengembangan Jiwa Kewirausahaan melalui Kreativitas dan Inovasi Siswa SMA Negeri 1 Indralaya Selatan Ogan Ilir - Ninin Non Ayu Salmah; Nisa' Ulul Mafra; Reina Damayanti (IKIP PGRI Bojonegoro, 2019)
Entrepreneurial spirit can be developed for school students from elementary, to college students. Students can create and innovate by aiming for market share starting from their own schools then develop more broadly. One of school at Indralaya understands that students need to be equipped with entrepreneurial spirit that is SMAN 1 South Indralaya Ogan Ilir Regency. This community service activities is aimed to develop the student’s entrepreneurial spirit of SMAN 1 Indralaya and defining efforts that have the potential to be developed by students of SMAN 1 Indralaya by utilizing their resources. The form of community service activities is counseling with a mechanism 1) presentation to students about the material of creativity, innovation and entrepreneurship 2) question and answer about the material that has been delivered. Participants showed their active participation in this stage which was shown by the spirit of discussion in groups so as to produce business proposals that were in accordance with the regional potential and community needs.Keywords: entrepreneurship, creativity, innovationABSTRAK Jiwa wirausaha dapat dikembangkan kepada siswa sekolah mulai dari tingkat dasar hingga mahasiwa di perguruan tinggi. Siswa dapat berkreasi dan berinovasi dengan membidik pangsa pasar mulai dari sekolahnya sendiri kemudian berkembang lebih luas. Salah satu sekolah di Indralaya memahami bahwa siswa perlu dibekali jiwa berwirausaha adalah SMAN 1 Indralaya Selatan Kabupaten Ogan Ilir. Kegiatan pengabdian kepada masyarakat ini bertujuan untuk mengembangkan jiwa kewirausahaan Siswa SMAN 1 Indralaya dan mendefinisikan usaha yang memiliki potensi untuk dikembangkan siswa SMAN 1 Indralaya dengan memanfaatkan sumber daya yang dimiliki. Bentuk kegiatan pengabdian masyarakat adalah penyuluhan dengan mekanisme 1)presentasi kepada siswa mengenai materi kreativitas, inovasi dan kewirausahaan 2)tanya jawab mengenai materi yang telah disampaikan. Peserta menunjukkan keaktifan dalam mengikuti tahap ini yang ditunjukkan dengan semangat berdiskusi dalam kelompok sehingga menghasilkan usulan usaha yang sesuai dengan potensi daerah dan kebutuhan masyarakat. Kata kunci : kewirausahaan, kreativitas, inovasi